One-year performance of thin-strut cobalt chromium sirolimus-eluting stent versus thicker strut stainless steel biolimus-eluting coronary stent: a propensity-matched analysis of two international all-comers registries. Issue 5 (20th October 2020) - Vlieger, Selina; Danzi, Gian B.; Kauer, Floris; Oemrawsingh, Rohit M.; Stojkovic, Sinisa; IJsselmuiden, Alexander J.J.; Routledge, Helen; Laanmets, Peep; Roffi, Marco; Fröbert, Ole; Baello, Pascual; Wlodarczak, Adrian; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Recent improvements in coronary stent design have focussed on thinner struts, different alloys and architecture, more biocompatible polymers, and shorter drug absorption times. This study evaluates safety and efficacy of a newer generation thin-strut cobalt chromium sirolimus-eluting coronary stent (SES, Ultimaster) in comparison with a second-generation thicker strut stainless steel biolimus-eluting stent (BES, Nobori) in percutaneous coronary intervention (PCI) practice. Methods: A propensity score analysis was performed to adjust for differences in baseline characteristics of 8137 SES patients and 2738 BES patients of two PCI registries (e-Ultimaster and NOBORI 2). An independent clinical event committee adjudicated all endpoint-related adverse events. Results: The use of SES, as compared with BES was associated with a significantly lower rate of myocardial infarction (MI) (1.2% vs 2.2%; P = 0.0006) and target vessel-related MI (1.1% vs 1.8%; P = 0.002) at 1 year. One-year composite endpoints of all predefined endpoints were lower in patients undergoing SES implantation (target lesion failure: 3.2% vs 4.1%; P = 0.03, target vessel failure: 3.7% vs 5.0%; P = 0.003, patient-oriented composite endpoint 5.7% vs 6.8%; P = 0.03). No significant differences between SES and BES were observed in all-cause death (2.0% vs 1.6%; P = 0.19), cardiac death (1.2% vs 1.2%; P = 0.76) or stent thrombosis (0.6% vs 0.8%; P = 0.43). Conclusions: These findings suggest an improved clinical safety and efficacy of a newer generation thin-strut SES as compared with a second-generation thicker strut BES.